Endoscopic Ultrasound-Guided Pancreatic Duct Intervention - Shimamura, Yuto (Clin Endosc, 2017)
Endoscopic ultrasound-guided pancreatic duct intervention (EUS-PDI) is an emerging endoscopic approach allowing access and intervention to the pancreatic duct (PD) for patients with failed endoscopic retrograde pancreatography (ERP) or patients with surgically altered anatomy. As opposed to biliary drainage for which percutaneous drainage is an alternative following failed endoscopic retrograde cholangiopancreatography (ERCP), the treatment options after failed ERP are very limited. Therefore, endoscopic ultrasound (EUS)-guided access to the PD and options for subsequent drainage may play an important role as an alternative to surgical intervention. However, this approach is technically demanding with a high risk of complications, and should only be performed by highly experienced endoscopists. In this review, we describe an overview of the current endoscopic approaches, basic technical tips, and outcomes using these procedures.